Outcome of pregnancy in sickle cell anemia patients with COVID-19 infection - Vaidyanathan Gowri; Tamima Al Dughaishi; Deepti Geetha; Marwa Al Riyami; Radhiya Alburaidi; Salam Al Kindi (Asian Journal of Transfusion Science)
Sickle cell anemia (SCA) is a multisystem disease, associated with increased risk for infection and thromboembolic disease, and pregnancy is a stressor for patients with SCA. In general, coronavirus disease 2019 (COVID-19) infection in SCA is associated with a favorable outcome. Literature of pregnancy in SCA with COVID is scarce. We report a case series study of pregnant women with SCA, who are confirmed positive for COVID-19 from May 2020 to March 2021. These patients showed generally mild-to-moderate disease and presented predominantly with fever and painful crisis. They showed a significant drop in Hb from baseline, and they received low-molecular-weight heparin prophylaxis (LMWH) and blood transfusion. The outcome of pregnancy is satisfactory, although the mean birth weight was significantly lower than that reported from the same SCA population.